ELectrophysiological mechanisms underlying the Inhibitory CArdiac syncope without asystolic significant pause: Therapeutic and prognostic implications. The ELICA randomized trial. Issue 31 (August 2018) - Sardu, Celestino; Marfella, Raffaele; Testa, Gianluca; Santamaria, Matteo; Sacra, Cosimo; Ranauro, Alfredo; Paolisso, Giuseppe; Rizzo, Maria Rosaria; Barbieri, Michelangela
Abstract: Background: The aim of this study was to investigate syncope recurrence in patients with a 2A cardioinhibitory response to the head up tilt testing (HUT). Methods: In this study, we enrolled 72 consecutive patients affected by syncope with cardioinhibitory response without asystolic significant pause to HUT (2A type). In these patients, we randomly performed electrophysiological study (ES). In case of sino-atrial node, atrio-ventricular node dysfunction, and sustained arrhythmias induction, the ES resulted positive. ES was positive in 9 patients (group A), then treated by catheter ablation, and/or by devices implants. Otherwise, ES resulted negative (group B), and these patients did not receive an interventional treatment. However, after ES, we evaluated syncope recurrence during 360 days follow-up. Results: There was a lower statistical significant syncope recurrence at follow-up, comparing group A to group B of patients [n of events 9 (40.9%) vs 8 (57.1%), P  < .05]. At multivariate analysis, ES result was the only factor predicting syncope recurrence at follow-up (hazard ratio = 27.63, 95% confidence interval = 1.02–54.24, P  < .005). Conclusion: The positivity to ES study, and successful interventional therapies may reduce the burden of syncope recurrence at 360 days follow-up in 2A HUT subjects. Clinical trial number: NCT02861274.